Methodology of pharmacogenetics research: Casecontrol studies - Oscanoa , Teodoro J. (2022)
Pharmacogenetics studies the association between the pharmacological phenotype of an individual with his/her genetic constitution. Case-control studies is a commonly used methodology when performing pharmacogenetics research. This design analyses the frequency of genetic variants in cases; that is, of those patients who have a particular phenotype (outcomes or results) compared with controls. For obtaining adequate methodological quality in pharmacogenetic case-control studies, it is important to work with precise phenotypes, have adequate case and control selection and appropriate sample size; select an adequate methodology for the identification of genetic variants, analyze the results using Hardy-Weinberg Equilibrium (HWE); and interpret the results considering the possibility of a phenoconversion phenomenon.